2016
DOI: 10.1002/ana.24745
|View full text |Cite
|
Sign up to set email alerts
|

Video gaming in school children: How much is enough?

Abstract: Objective: Despite extensive debate, the proposed benefits and risks of video gaming in young people remain to be empirically clarified, particularly as regards an optimal level of use. Methods: In 2,442 children aged 7 to 11 years, we investigated relationships between weekly video game use, selected cognitive abilities, and conduct-related problems. A large subgroup of these children (n 5 260) was further examined with magnetic resonance imaging approximately 1 year later to assess the impact of video gaming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 41 publications
2
45
0
1
Order By: Relevance
“…This appears to be the current trend, as will be shown further below in this review. While a reasonable and well-balanced use of computers and digital media by children may contribute positively to the development of academic, cognitive, and social skills [172][173][174][175], such benefits are severely overshadowed by the tangible risks of an excessive exposure to digital environments as revealed by the large majority of facts and figures accounted for in this review. The concerns expressed herein, and the model proposed at the end, acquire their full significance under the light of publically available population statistics [1, 26-29, 69, 75] showing an alarming trend towards increasingly younger children spending increasingly long hours indoors, invisibly "tethered" to digital devices [26,27,28] and a steep increase in adolescent suicide rates in the US [75] and possibly other countries for which no such statistics are publically available.…”
Section: Resultsmentioning
confidence: 95%
“…This appears to be the current trend, as will be shown further below in this review. While a reasonable and well-balanced use of computers and digital media by children may contribute positively to the development of academic, cognitive, and social skills [172][173][174][175], such benefits are severely overshadowed by the tangible risks of an excessive exposure to digital environments as revealed by the large majority of facts and figures accounted for in this review. The concerns expressed herein, and the model proposed at the end, acquire their full significance under the light of publically available population statistics [1, 26-29, 69, 75] showing an alarming trend towards increasingly younger children spending increasingly long hours indoors, invisibly "tethered" to digital devices [26,27,28] and a steep increase in adolescent suicide rates in the US [75] and possibly other countries for which no such statistics are publically available.…”
Section: Resultsmentioning
confidence: 95%
“…Moderate use might even be advantageous for students, the so-called "Goldilocks Effect" 3 , posing no real risk to mental well-being of adolescents, although this can depend on factors such as type of media used and when it is used (i.e. during the week or weekend) (Przybylski and Weinstein, 2017 [26]). Negative outcomes have been associated with media consumption in excess of 6 hours per day (Ferguson, 2017[116]), however the association with mental well-being is small (Przybylski and Weinstein, 2017[26]).…”
Section: Summing Upmentioning
confidence: 99%
“…This suggests moderate engagement in online and digital activities might actually be beneficial in terms of subjective mental well-being and adolescent connectedness, whereas too much or too little might prove detrimental (Przybylski and Weinstein, 2017[26])…”
mentioning
confidence: 99%
“…Many previous studies have demonstrated that video game training is associated with improvements in working memory, mental processing speed, multitasking, attentional control and other cognitive abilities . On the other hand, excessive video game playing or exposure to improper game contents, especially for school children and adolescences, may have negative effects, including poor performance and misconducts in school , increased propensity for violence or risky behaviors , poor decision‐making ability , impaired impulsivity inhibition , emotion management problem and even online game addiction (OGA) .…”
Section: Introductionmentioning
confidence: 99%